Avaliação do efeito da deleção genética do receptor MrgD sobre a expressão gênica no tecido adiposo marrom de camundongos C57BL6/J - Gabriela Cavazza Cerri (2021)
Alamandine is a heptapeptide part of the renin-angiotensin system (RAS). The amino acid sequence of alamandine (Ala-Arg-Val-Tyr-Ile-His-Pro) is similar to the amino acid sequence of ANG-(1-7) (Asp-Arg-Val-Tyr-Ile-His-Pro), except for the presence of alanine in the place of aspartate. In addition to the structure, the effects of alamandine are also similar to the effects of Ang-(1-7). Despite the similarities, the effects of alamandine are mediated by the MrgD receptor. The MrgD receptor is expressed in a variety of tissues e.g. dorsal root ganglia, artery, bladder, cerebellum, heart, and adipose tissue. The other RAS receptors (MAS, AT1R and AT2R) are also expressed in a wide variety of organs, including white and brown adipose tissues. This localized expression in endocrine tissues provides a great influence of the RAS on the metabolism. In the brown adipose tissue (BAT), the ECA2/Ang-(1-7) axis activity promotes increased energy expenditure and activity of several markers such as AMPK, UCP1 and PGC1a. Our first results indicated that the alamandine receptor, MrgD, may also have an influence on BAT, as we observed that MrgD/KO animals have extremely decreased BAT and obese C57BL6/J mice show decreased expression of MrgD in BAT. Therefore, this tissue and this receptor caught our attention. Since we have no studies on the effect of the alamandina/MrgD axis on metabolism, a technique that promotes comprehensive results allows for a better north and can provide different lines for future work. In this sense, the RNA sequencing technique for RNA extracted from BAT of obese and lean MrgD/KO mice was performed. Obesity was induced by a high-glucose diet (HG) for 8 weeks. Obesity induced transcriptional changes in the BAT of WT HG animals related to increased metabolism and adaptive thermogenesis. The expression of the MrgD receptor is essential for a HG diet response, since the MrgD/KO HG group failed in regulating more than 1000 genes compared to the MrgD/KO ST group. In the absence of the MrgD receptor BAT transcripts are deeply downregulated decreasing the expression of over 400 genes. MrgD/KO animals decreased the expression of thermogenic markers and increased the expression of fibrosis markers in the comparison between MrgD/KO HG vs WT HG. In addition, the absence of the MrgD receptor promotes a tendency to regulate several pathways e.g., calcium signaling, electron transport chain, thermogenesis, and cardiomyopathies. According to the analysis we found some of the main targets of the alamandin/MrgD axis: AMPK, ion channels and components of the extracellular matrix.